Protective Effects of Exogenous Melatonin on Cisplatin- Induced Acute Nephrotoxicity in Rats - Mahmood, Kochar Idrees; Kadir, Sardar Mirza (Sulaimani Journal for Pure and Applied Sciences, 2017)
This study was planned to investigate the consequences of exogenous administration of melatonin on the amelioration of some biochemical variables in cisplatin (CP)-induced acute nephrotoxicity in rats. Twenty-four male rats weighing 300-350g were used. Housing of the animals and the experiment were achieved and the rats were -housed in the Department of Biology /College of Science/ Sulaimani University. The Animals were divided into three groups (n=5); control group (receiving prepared standard chow for rats and water ad libitum); model group(The animals administered a single intraperitoneal (i.p) dose of CP (8 mg/kg BW.); and the third group in addition to CP injection the animals were supplemented with melatonin (180 mg/kg food) at the same day of CP- injection for five days. Finally, the blood specimen was taken using cardiac puncture. The studied parameters include Malondialdehyde (MDA), serum creatinine, serum urea, serum total bilirubin, serum albumin, serum electrolytes (Ca+2, Na+ and K+), as well as some hematological parameters (WBC, RBC, HCT, HGB). Our results showed significant (P<0.05) elevation in the serum level of MDA,, creatinine, urea and total bilirubin in model group. On the other hand, the WBC count was also increased significantly (P<0.01), whereas there was no significant alterations in the level of calcium, sodium, and potassium. The outcome of our study indicated that the melatonin administration in injected rats for five days significantly (P<0.01) improved the elevated serum levels of MDA, creatinine, urea, total bilirubin and WBC count. In conclusion, this study confirmed that melatonin has protective effects of ameliorating the nephrotoxicity induced by cisplatin in rat.
Keywords: Melatonin; Cisplatin; Nephrotoxicity; Antioxidant